2019
DOI: 10.5430/rwe.v10n2p117
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Implementing Information and Communications Technology (ICT) Based Online Learning in Chinese Independent High Schools (CIHS) in Malaysia

Abstract: The use of ICT in the teaching and learning process is one of the most discussed topics in education for the past twenty years. It has, particularly, put education in Chinese Independent High Schools (CIHS) in Malaysia into a more challenging place due to their distinctions that revolve around self-funding, medium of instruction and syllabus. Past studies have indicated that most teachers had positive attitudes towards ICT integration in education. However, there are also some barriers that have prevented them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, Ahmad et al (2020) discovered that although 65.4% of the 156 accounting teachers in Perak, Kedah, and Selangor felt that FrogVLE produced an interesting learning environment, 34.6% of them had never utilised it in their teaching due to the infrastructure at the schools did not support the use of the applications. Apart from that, a quantitative study conducted by Vien et al (2019) on Chinese Independent High School (CIHS) in Malaysia showed similar results in which an unstable internet connection became the major challenge when using ICT in the learning process.…”
Section: Literature Review Ict Infrastructurementioning
confidence: 78%
“…Meanwhile, Ahmad et al (2020) discovered that although 65.4% of the 156 accounting teachers in Perak, Kedah, and Selangor felt that FrogVLE produced an interesting learning environment, 34.6% of them had never utilised it in their teaching due to the infrastructure at the schools did not support the use of the applications. Apart from that, a quantitative study conducted by Vien et al (2019) on Chinese Independent High School (CIHS) in Malaysia showed similar results in which an unstable internet connection became the major challenge when using ICT in the learning process.…”
Section: Literature Review Ict Infrastructurementioning
confidence: 78%
“…The lack of institutional support and policies was another significant challenge identified (Abugohar et al, 2019;Al-Mubireek, 2020;Ashely-Welbeck & Vlachopoulos, 2020;Vien et al, 2019). The absence of clear guidelines and support systems within educational institutions may discourage teachers from exploring and adopting digital tools in their English language teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Nurohmat (2021) describes that English learners can achieve a higher score in online learning than in a traditional classroom. Similarly, Vien et al (2019) mention that language teachers perceive their students to better comprehend the language learning material delivered through online learning platforms than when taught traditionally. Nevertheless, many factors can contribute to students' achievement in online learning besides online learning platforms, one of which is self-efficacy.…”
Section: The Use Of Online Learning Platformsmentioning
confidence: 99%